School Facilities and Internal Efficiency of Public Secondary Schools in Oyo State. - Afolabi, Rebecca A.; Sofoluwe, Abayomi O. (International Journal of Educational Management, 2021)
The study investigated school facilities and internal efficiency of public secondary schools in Oyo State. The research design was descriptive of the survey type. The population consists of all 640 public secondary schools and 13,010 teachers in Oyo State. Seventy-five (75) public secondary schools were selected using simple random sampling technique. A total of 1,500 teachers were used for the study using simple random sampling technique. 'Assessment of School Facilities Questionnaire' (ASFQ). West African Senior School Certificate Examination (WASSCE) results for the period of five years between 2014- 2018 for students with five credits including Mathematics and English were used to measure internal efficiency of public secondary schools. The instrument on school facilities was validated and tested for reliability. The reliability coefficient was found to be 0.81. Three research questions were raised to guide the study and two hypotheses were formulated. Data collected were analysed using simple percentage and frequency count. Pearson Product Moment Correlation Statistic was used to test the hypothesis at 0.05 level of significance. The findings showed that; virtually all facilities were inadequate and there was significant relationship between school facilities and internal efficiency of secondary schools in Oyo State. Based on the findings, in order to improve efficiency of public secondary schools it was recommended that Government and/or State ministry of Education should seek for assistance of philanthropist, big companies, financial institutions and the Education Trust Fund (ETF) in providing classrooms, laboratories, laboratory equipment and other facilities necessary for effective teaching-learning process in our school. Likewise, the schools managers should try to maintain and manage the available instructional materials such as charts, slides, public address system, filmstrips, models and projector facilities provided in the school.